2019
DOI: 10.7589/2018-05-124
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Rabbit Hemorrhagic Disease Virus GI.2/RHDV2/b in the Mediterranean Pine Vole (Microtus duodecimcostatus) and White-Toothed Shrew (Crocidura russula)

Abstract: The European wild rabbit ( Oryctolagus cuniculus) is a key prey species on the Iberian Peninsula, and several predator species that are at risk of extinction are dependent on them as prey. A new rabbit hemorrhagic disease (RHD) virus genotype (GI.2/RHDV2/b) emerged in 2010 and posed a threat to wild rabbit populations. During a survey aimed at investigating RHD epidemiology in wild rabbits, GI.2/RHDV2/b was detected by duplex real-time PCR in carcasses of one Mediterranean pine vole ( Microtus duodecimcostatus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…The genome characteristics and phylogeny of Alpine musk deer RHDV GS/YZ indicated that this virus is a G2 RHDV, showing close genetic and evolutionary relationships with previously reported G2 RHDV isolates ( Figure 5 ). To date, all other RHDV strains in the G2 group were isolated from rabbits, and no spillover of these viruses to other animal populations was found [ 37 , 38 , 39 ]. To understand the potential reasons for this spillover, we compared the amino acid differences of RHDV GS/YZ and 19 other G2 RHDV strains.…”
Section: Discussionmentioning
confidence: 99%
“…The genome characteristics and phylogeny of Alpine musk deer RHDV GS/YZ indicated that this virus is a G2 RHDV, showing close genetic and evolutionary relationships with previously reported G2 RHDV isolates ( Figure 5 ). To date, all other RHDV strains in the G2 group were isolated from rabbits, and no spillover of these viruses to other animal populations was found [ 37 , 38 , 39 ]. To understand the potential reasons for this spillover, we compared the amino acid differences of RHDV GS/YZ and 19 other G2 RHDV strains.…”
Section: Discussionmentioning
confidence: 99%
“…The fecal-oral transmission route and the persistent infection of non-pathogenic lagoviruses was elucidated by RT-qPCR [ 27 , 160 ]. Furthermore, it allowed the detection of low amounts of GI.2 in carcasses of non-target species, such as the Mediterranean pine vole ( Microtus duodecimcostatus ) and the white-toothed shrew ( Crocidura russula ) [ 163 ]. Even acknowledging that the number of genome copies is not directly proportional to the number of infectious particles, RT-qPCR is also useful to confirm successful viral replication in inoculation trials [ 75 , 164 ].…”
Section: Real-time Quantitative Rt-pcrmentioning
confidence: 99%
“…Epidemiological research on RHD is an important point in monitoring the current situation. Calvete et al [19] carried out studies using real-time PCR, which showed the presence of the virus in the found carcasses of Mediterranean voles (Microtus duodecimcostatus) and in two specimens of shrews (Crocidura russula). Thus, it has been shown that within L. europaeus GI.2, there can be passive transmission of the virus to species beyond the Lagomorph order [19].…”
Section: Primermentioning
confidence: 99%
“…Calvete et al [19] carried out studies using real-time PCR, which showed the presence of the virus in the found carcasses of Mediterranean voles (Microtus duodecimcostatus) and in two specimens of shrews (Crocidura russula). Thus, it has been shown that within L. europaeus GI.2, there can be passive transmission of the virus to species beyond the Lagomorph order [19]. The appearance of the L. europaeus GI.2 virus caused a great deal of confusion in many countries, making it necessary to monitor the evolution and spread of this pathogen in wild populations.…”
Section: Primermentioning
confidence: 99%